Evaluation of Anticancer Potential of Mimosa diplotricha Ethanolic Leaf Extract on N-Methyl-NNitroso Urea Induced Colorectal Carcinogenesis in Wistar Albino Rats - Madathil, Sri Rashmy; Kannappan, Poornima; Muthusami, Sridhar; Muneeswari, Perumalsamy; Periyasamy, Loganayaki (Indian Journal of Pharmaceutical Education and Research, 2022)
Background: Colorectal Cancer, (CRC) ranks third among global cancer incidence statistics and occupies fourth position as far as cancer related death is concerned and the aim of the study is to evaluate the therapeutic potential of Mimosa diplotricha ethanolic leaf extract in chemically induced colorectal carcinogenesis in Wistar albino rats. Materials and Methods: CRC was induced by intrarectal instillation of N-Methyl-N-Nitrosourea (MNU), 2mg per rat in 0.5ml of distilled water three times a week for five weeks. Rats were grouped as control, induced, induced and standard drug treated (15mg/kg.bw), induced and plant extract treated (in two doses 200mg/kg.bw and 400mg/kg.bw) and normal rats with respective plant extract treatment (200mg/kg.bw and 400mg/kg.bw). Treatment were carried out for 60 days followed which animals were euthanized and serum markers, oxidative stress, microbial enzymatic, histological and immunohistochemical parameters were analysed. Results: M. diplotricha was found to be effective in the down regulation of serum inflammatory and tumour markers like tumour necrosis factor alpha, transforming growth factor beta, carcinoembryogenic antigen and colon cancer specific antigen-4 levels. Oxidative stress parameters and histological data also supported the therapeutic efficacy of M. diplotricha. Expression of anti-apoptotic protein Bcl-2 was also found be downregulated in induced animals treated with M. diplotricha as evident from immunohistochemical data. Conclusion: The results of present research suggest that M. diplotricha ethanolic leaf extract showed a significant therapeutic potential against chemically induced colorectal carcinogenesis.
Keywords: CRC; Wistar rats; MNU; Mimosa diplotricha; Serum markers; Bcl-2